PERNYATAAN KALA DAN ASPEK DALAM BAHASA ARAB: ANALISIS SEMANTIK VERBA - Tajudin Nur (Arabi : Journal of Arabic Studies, 2018)
This research was a qualitative research using structural linguistic method. The findings showed that the conjugation of the perfect verbs (madhi) into imperfect verbs (mudhari’) can reveal the concept of semantic time and aspect. It was found that the conjugation of verb from perfect (madhi) to imperfect (mudhari’) expresses semantical concept of tense and aspect. Perfect verb expresses past tense, present tense, future tense, and perfective aspect, while imperfect verb expresses present tense, future tense, and imperfective aspect. The other constituents which had a role in expressing tense and aspect were auxiliary verb of kana, the particles of qad, sawfa, lan, and sa- prefix. The auxiliary verb of kana had a role to express past tense in the case of equational sentence or if it precedes imperfect verb, while if it precedes  perfect verb, it expresses perfective aspect. The particle of qad expresses perfective aspect if it precedes perfect verb (madhi), while the particle of sawfa, lan, and sa- prefix express future tense. In addition, to clarify the tense in Arabic adverb of time standing beside the verb also was used.